ANALISIS YURIDIS TERHADAP JAMINAN SOSIAL KESEHATAN OLEH BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) TERHADAP MASYARAKAT YANG TIDAK MAMPU - Abd Rahmad (Normative Jurnal Ilmiah Hukum, 2018)
Implementation of Community Health Insurance for poor people, not all are affordable to be able to enjoy and utilize the objectives of the Social Security Organizing Board (BPJS) in the category of Contribution Aid Recipients (PBI). In order to fulfill the mandate of the Law the Government established a Social Security Organizing Body (BPJS). The Government's policy in guaranteeing the poor by issuing the BPJS program in the PBI category with the various goals that have been announced has not yet been understood by the people who get the program. This can be seen from the utilization of BPJS which is not yet optimal. Constraints faced are still low public education which is less able to influence the pattern of BPJS utilization from the low level of public knowledge about the functions and procedures of BPJS. The solution is to re-collect the underprivileged people by the Government in Padang City.